Effects of Maternal Stress on Measures of Anxiety and Fearfulness in Different Strains of Laying Hens - Peixoto, Mariana R. L. V.; Karrow, Niel A.; Newman, Amy; Widowski, Tina M. (Frontiers in Veterinary Science, 2020)
Maternal stress can affect the offspring of birds, possibly due to hormone deposition in the egg. Additionally, phenotypic diversity resulting from domestication and selection for productivity has created a variety of poultry lines that may cope with stress differently. In this study, we investigated the effects of maternal stress on the behavior of different strains of laying hens and the role of corticosterone as its mediator. For this, fertilized eggs of five genetic lines—two brown (Brown 1 and 2), two white (White 1 and 2), and one pure line White Leghorn—were reared identically as four flocks of 27 birds (24F: 3M) per strain. Each strain was equally separated into two groups: Maternal Stress (“MS”), where hens were subjected to a series of daily acute psychological stressors for 8 days before egg collection, and “Control,” which received routine husbandry. Fertile eggs from both treatments were collected at three different ages forming different offspring groups that were treated as replicates; additional eggs from Control were injected either with corticosterone diluted in a vehicle solution (“CORT”) or just “Vehicle.” Eggs from each replicate were incubated and hatched, and offspring (N = 1,919) were brooded under identical conditions. To measure the effects of maternal stress on anxiety and fear-like behavior, offspring were subjected to a social isolation test (SI) between 5 and 10 days of age and a tonic immobility test (TI) at 9 weeks of age. Compared to Control, MS decreased the number of distress vocalizations emitted by White 2 in SI. No effects of MS were observed in TI, and no effects of CORT were observed in any tests. Overall, brown lines vocalized more in SI and remained in TI for a longer duration than white strains, suggesting genetic differences in fear behavior. Females vocalized more than males in TI and showed a trend toward significance for the same trait in SI. Overall, results suggest that the effects of maternal stress on fearfulness are not directly mediated by corticosterone. Moreover, it highlights behavioral differences across various strains of laying hens, suggesting that fear responses are highly dependent on genotype.